2014
DOI: 10.14260/jemds/2014/1857
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices of Infant Feeding Practices Among Rural Women in Eastern India

Abstract: BACKGROUND:Poor infant feeding practices and their consequences are one of the world's major problems and a serious obstacle to social and economic development. Breastfeeding is one of the most important determinants of child survival, birth spacing, and the prevention of childhood infections. The beneficial effects of breastfeeding depend on its initiation, duration, and the age at which the breastfed child is weaned. Breastfeeding practices vary among different regions and communities.AIMS AND OBJECTIVES: To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The poor level of nutrition knowledge observed in this study is in contrast with findings from other nutrition studies. For instance, Anand and Puri (2013) and Das and Mukherjee (2014) It was interesting to note that attitude of the respondents toward consumption of wild fruits and vegetables was good. This observation could be explained by the fact that wild fruits and vegetables contribute significantly to household food security in the study area (Loki & Ndyomugyenyi, 2016b;Oryema et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor level of nutrition knowledge observed in this study is in contrast with findings from other nutrition studies. For instance, Anand and Puri (2013) and Das and Mukherjee (2014) It was interesting to note that attitude of the respondents toward consumption of wild fruits and vegetables was good. This observation could be explained by the fact that wild fruits and vegetables contribute significantly to household food security in the study area (Loki & Ndyomugyenyi, 2016b;Oryema et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Anand and Puri (2013) and Das and Mukherjee (2014) found that women's nutritional knowledge on HIV management and infant feeding practices was good among urban and rural Indian population, respectively. This implies that nutritional knowledge varies with context under which it is being applied.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that nutrition education capacity building provided to caregivers during armed conflict emergency situation and immediately during the post-conflict recovery period is largely retained in terms of knowledge and attitude but limitedly translated into practice. The inability of caregivers to translate good nutritional knowledge and attitude to good nutrition behavior is in consonant with the generally known phenomenon that good nutritional knowledge and attitude may not necessarily guarantee good nutritional practices (Anand & Puri, 2013;Das & Mukherjee, 2014;Hasnain, Majrooh, & Anjum, 2013;Salarkia, Amini, Abdollahi, Eshrati, & Neyestani, 2014), thus suggesting that other factors could be directly responsible or playing a moderating role. Nevertheless, none of the socio-demographic factors investigated in this study could predict good nutritional practices (Table 5).…”
Section: Discussionmentioning
confidence: 81%
“…22 Ratan and Mukherjee et al reported that 64% of mothers had a good opinion about colostrum. 23 Appropriate knowledge about breastfeeding initiation time among vaginal delivery and cesarean mothers' were 76.9% and 65.2%, respectively. 24 Harnagle et al, in his study, disclosed that 63.6% of the women breastfed their newborn within 6 hours of birth.…”
Section: Colostrum and Initiation Of Breastfeedingmentioning
confidence: 95%